Conditional Expression of the Small GTPase ArfA Impacts Secretion, Morphology, Growth, and Actin Ring Position in Aspergillus niger - Fiedler, Markus R. M.; Cairns, Timothy C.; Koch, Oliver; Kubisch, Christin; Meyer, Vera (Frontiers in Microbiology, 2018)
In filamentous fungi, growth and protein secretion occurs predominantly at the tip of long, thread like cells termed hyphae. This requires coordinated regulation of multiple processes, including vesicle trafficking, exocytosis, and endocytosis, which are facilitated by a complex cytoskeletal apparatus. In this study, functional analyses of the small GTPase ArfA from Aspergillus niger demonstrate that this protein functionally complements the Saccharomyces cerevisiae ARF1/2, and that this protein is essential for A. niger. Loss-of-function and gain-of-function analyses demonstrate that titration of arfA expression impacts hyphal growth rate, hyphal tip morphology, and protein secretion. Moreover, localization of the endocytic machinery, visualized via fluorescent tagging of the actin ring, was found to be abnormal in ArfA under- and overexpressed conditions. Finally, we provide evidence that the major secreted protein GlaA localizes at septal junctions, indicating that secretion in A. niger may occur at these loci, and that this process is likely impacted by arfA expression levels. Taken together, our results demonstrate that ArfA fulfils multiple functions in the secretory pathway of A. niger.